Study of Bridge Upper Structure Design with Composite Box Girder for Coal Mining Trailer Loads: (Case Study: Belayan River - Kutai Kartanegara) - Donald Essen; Sudrajat (NAROTAMA UNIVERSITY, Indonesia, 2021)
In the process of mobilizing coal on mine hauling road, which have to cross rivers, a bridge that is capable of carrying the traffic load from the mining truck is required. This study aims to plan a bridge structure with a composite box girder for coal mine trailer loads. In this study, the authors conducted a loading analysis based on SNI 1725 (2016) and planning the cross-sectional proportions based on the applicable provisions in (AASHTO, 2017). This research was carried out in several stages, starting from design of section proportions, flexure design, shear design, stiffener and shear connector. The results of this study show that the composite box girder can be applied at the research location and also the proportion of the cross-section that is able to withstand traffic loads working on the bridge structure with a nominal moment resistance value of 78856.13 kN.m which is greater than the ultimate moment due to loading that occurs with a value of 66912.64 kN.m.